2016
DOI: 10.1007/s00005-016-0405-y
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor NF-κB: An Update on Intervention Strategies

Abstract: The nuclear factor (NF)-κB family of transcription factors are ubiquitous and pleiotropic molecules that regulate the expression of more than 150 genes involved in a broad range of processes including inflammation, immunity, cell proliferation, differentiation, and survival. The chronic activation or dysregulation of NF-κB signaling is the central cause of pathogenesis in many disease conditions and, therefore, NF-κB is a major focus of therapeutic intervention. Because of this, understanding the relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
82
1
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(84 citation statements)
references
References 162 publications
0
82
1
1
Order By: Relevance
“…GSK-3β was phosphorylated when the signaling pathway of PI3K/ AKT is activated. NF-κB is found to be involved in cellular processes and to control DNA transcription in almost all animal cell types [28]. A dysregulated NF-κB is linked to cancer, inflammation, autoimmune disease, and etc .…”
Section: Discussionmentioning
confidence: 99%
“…GSK-3β was phosphorylated when the signaling pathway of PI3K/ AKT is activated. NF-κB is found to be involved in cellular processes and to control DNA transcription in almost all animal cell types [28]. A dysregulated NF-κB is linked to cancer, inflammation, autoimmune disease, and etc .…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that NF-κB is generally involved in IL-8 gene expression [37], but in our study the addition of an NF-κB inhibitor did not reduce IL-17F-induced IL-8 expression. Consistent with this, previous reports have demonstrated that cadmium or rhinovirus induced IL-8 expression through an NF-κB-independent pathway in airway epithelial cells [38, 39].…”
Section: Discussioncontrasting
confidence: 85%
“…When receiving external stimuli, the inhibitor of NF-κB kinase (IKK) is activated to phosphorylate IκB, and then promotes the ubiquitination and degradation of IκB. Subsequently, p65/p50 heterodimers are released to translocate into the nucleus, and regulate the transcription of the downstream genes [21, 22]. Postmortem demonstrated that the proportion of NF-κB (p65)-immunoreactive dopaminergic neurons in idiopathic PD patients was 70-fold higher than that in control subjects [23].…”
Section: Discussionmentioning
confidence: 99%